Acute social defeat during adolescence promotes long-lasting aggression through activation of the medial amygdala - Mojahed, Nooshin; Adjei, Magdalene; Qasem, Elana; Aaflaq, Sophia; Adu, Temitope; Jacobs, Jessica T.; Richardson, Ben D.; Nordman, Jacob C. (Frontiers in Neuroscience, 2024)
Traumatic stress, particularly during critical developmental periods such as adolescence, has been strongly linked to an increased propensity and severity of aggression. Existing literature underscores that being a victim of abuse can exacerbate aggressive behaviors, with the amygdala playing a pivotal role in mediating these effects. Historically, animal models have demonstrated that traumatic stressors can increase attack behavior, implicating various amygdala nuclei. Building on this foundation, our previous work has highlighted how traumatic stress invokes long-lasting aggression via an excitatory pathway within the posterior ventral medial amygdala (MeApv). In the current study, we sought to further delineate this mechanism by examining the effects of acute social defeat during adolescence on aggressive behaviors and neural activation in mice. Using a common social defeat paradigm, we first established that acute social defeat during late adolescence indeed promotes long-lasting aggression, measured as attack behavior 7 days after the defeat session. Immunolabeling with c-Fos demonstrated that acute social defeat activates the MeApv and ventrolateral aspect of the ventromedial hypothalamus (VmHvl), consistent with our previous studies that used foot shock as an acute stressor. Finally, chemogenetically inhibiting excitatory MeApv neurons during social defeat significantly mitigated the aggression increase without affecting non-aggressive social behavior. These results strongly suggest that the MeApv plays a critical role in the onset of aggression following traumatic social experience, and offer the MeA as a potential target for therapeutic interventions.